Physiological and genetic variation in Nitrogen Use Efficiency of wheat - Nitnavare, Rahul (2024)
Wheat is one of the three main cereal crops in the world and its demand is increasing with increasing population. The excess use of nitrogen (N) fertilisers causes serious environmental impacts including nitrate leaching into ground water, eutrophication of water bodies, and global warming due to nitrous oxide emissions. Therefore, a key breeding target in wheat cultivation is enhancing Nitrogen-use efficiency (NUE). In wheat, there is relatively small genetic variation in adapted elite germplasm in N-uptake efficiency (NUpE) and N-utilisation efficiency (NUtE), which are the two key components of the NUE. Therefore, this study aims to identify novel variation for traits and associated gene markers for NUE using more diverse germplasm. The main objectives of the present study were: (i) Screening of diverse sets of hexaploid wheat genetic resources including landraces (from AE Watkins collection) x elite cultivar Paragon crosses, synthetic hexaploid wheat-derived lines, and elite cultivars for novel trait variation for improved NUE and (ii) the identification of haplotypes to enable development of markers for NUE and related traits. Initially, a diverse set of 64 Near-Isogenic Lines was screened for variation in NUE, NUpE, NUtE and associated traits including Grain Yield (GY), Above-Ground Dry Matter (AGDM), Nitrogen Harvest Index (NHI), Grain N Uptake, Grain Protein Content (GPC) and photosynthesis traits, e.g. Flag-leaf Photosynthesis Rate (Amax) and Stomatal Conductance (gs), in field experiments under optimal N supply at two locations, i.e., Rothamsted Research and Sutton Bonington in 2018-19. Several NILs having Watkins alleles for QTLs for traits such as Grain yield (GY), Above-Ground Dry Matter (AGDM) and Grain-Fill Period Thermal Time (GFPTT) showed higher values for NUE as compared to Paragon. The performance of the NILS for the photosynthesis traits flag-leaf Amax and gs was also considered for the selection of a sub-set of lines as they directly influence biomass, GY and NUE. Therefore, 18 NILs along with parents (Paragon and Robigus) were shortlisted after evaluating performance at both the experimental sites for studying response to N availability in high N and low N treatments. Phenotyping of the 18 shortlisted NILs under high and low N conditions (High N 200 kg N ha-1 and Low N 50 kg N ha-1 respectively) to determine lines suitable for carrying out a RNA-seq based transcriptomics study was then performed in field experiments at Rothamsted Research for two consecutive years 2020 and 2021. These experiments were carried out and then five genotypes were shortlisted for the RNAseq-based transcriptomics field study. After analysing cross-year results, NILs which showed significant correlation with NUE, NHI, NUpE, GPC and NUtE traits when compared with the corresponding Paragon allele were shortlisted. The five genotypes shortlisted included three Paragon × Watkins landrace NILs for QTLs for above-ground dry matter (PW141-10-Q7D-AGDM-W), Grain Yield (PW468-1-Q5A-COMGRWT-W) and Straw Yield (PW292-1-Q3A-COMSTR-W), the Paragon parent and one synthetic hexaploid wheat (SHW) derived line 58. (iii) To Identify candidate genes for NUE through transcriptomics of flag-leaf tissue at post-anthesis stage of the five selected genotypes under high N and low N conditions, RNA-seq based transcriptomics was performed with the flag leaves of these genotypes in a field experiment in 2021 at Rothamsted Research. The RNAseq data were analysed to identify the candidate genes having differential expression under the two N treatments. Several genes showed differential expression. However, Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways enrichment analysis suggested the following keys genes from various biological processes including photosynthesis: chlorophyll a-b binding protein 1B, glyceraldehyde-3-phosphate dehydrogenase, cytochrome P450, tress response: proline-rich receptor-like protein kinase, BED zinc finger , FBD-associated F-box protein, amino acid metabolism: tryptophan decarboxylase 1, aspartic proteinase, LRR receptor-like serine/threonine-protein kinase. These candidate genes may contribute to the development of precise SNP markers for NUE traits for deployment in marker-assisted selection in wheat breeding ultimately leading to new cultivars with higher NUE and grain yields.